2014
DOI: 10.1016/j.febslet.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

TALEN‐mediated mutagenesis in zebrafish reveals a role for r‐spondin 2 in fin ray and vertebral development

Abstract: a b s t r a c t R-spondin (Rspo) encodes a multi-domain protein that modulates the Wnt-signaling pathway. Two distinct rspo2 zebrafish mutants were generated by TALEN-mediated mutagenesis: a null mutant, rspo2 null , lacking all functional domains, and a hypomorphic mutant, rspo2 tsp , lacking the two N-terminal domains. Mutants were analyzed mainly for abnormalities in the skeletal system. Fin ray skeletons were formed normally in the rspo2 tsp mutants, but were absent from the rspo2 null mutants. Hypoplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
2
14
0
1
Order By: Relevance
“…We mapped the spatial and temporal expression patterns of Rspo2 in C. semilaevis and determined its function during embryogenesis. qRT-PCR revealed that CsRspo2 was barely transcribed before gastrulation, which is consistent with the pattern in zebrafish (Tatsumi et al, 2014), where Rspo2 mRNA was not detected until zygotic expression begins at the 75% epiboly stage. Moreover, the CsRspo2 expression pattern in different tissues showed similarities with that in mouse and zebrafish (Nam et al, 2007b;Aoki et al, 2008;Tatsumi et al, 2014), which suggests a common function for Rspo2 in diverse species.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We mapped the spatial and temporal expression patterns of Rspo2 in C. semilaevis and determined its function during embryogenesis. qRT-PCR revealed that CsRspo2 was barely transcribed before gastrulation, which is consistent with the pattern in zebrafish (Tatsumi et al, 2014), where Rspo2 mRNA was not detected until zygotic expression begins at the 75% epiboly stage. Moreover, the CsRspo2 expression pattern in different tissues showed similarities with that in mouse and zebrafish (Nam et al, 2007b;Aoki et al, 2008;Tatsumi et al, 2014), which suggests a common function for Rspo2 in diverse species.…”
Section: Discussionsupporting
confidence: 81%
“…qRT-PCR revealed that CsRspo2 was barely transcribed before gastrulation, which is consistent with the pattern in zebrafish (Tatsumi et al, 2014), where Rspo2 mRNA was not detected until zygotic expression begins at the 75% epiboly stage. Moreover, the CsRspo2 expression pattern in different tissues showed similarities with that in mouse and zebrafish (Nam et al, 2007b;Aoki et al, 2008;Tatsumi et al, 2014), which suggests a common function for Rspo2 in diverse species. High expression levels of CsRspo2 in the gill, brain and gonads may be related to its functions in dorsal neural tube development (Kamata et al, 2004;Nam et al, 2007b) and gonad differentiation .…”
Section: Discussionsupporting
confidence: 81%
“…9 To further investigate the role of Rspo2 during budding, we then analyzed the lateral line patterns of rspo2 homozygous mutant (rspo2−/−) fish. 13 Strikingly, the rspo2−/− fish lacked CLLs entirely ( Figure 1E,F) and showed a 30% reduction in ter2 0 ( Figure 1F), even in the presence of prospective ter2 0 precursor cells (data not shown). These phenotypes were in complete agreement with those when the PLL ganglion was ablated, 9 supporting the idea that axonderived Rspo2 is required for the proliferation of bud neuromasts through activating Wnt signaling.…”
Section: Axon-dependent or Independent Neuromast Formationmentioning
confidence: 83%
“…Furthermore, it was recently reported that Rspo2 serves as a direct antagonistic ligand for Znrf3/Rnf43 without Lgr receptors to regulate human limb development [65]. Rspo2-null zebrafish also displays skeletal malformations, including absence of fin ray skeleton and hypoplasia of the rib [66]. These findings suggest that Rspo2 is a key regulator of musculoskeletal development through Wnt signaling.…”
Section: R-spondin Signaling and Tissue Homeostasismentioning
confidence: 95%